E × B flow driven electron temperature bifurcation in a closed slot divertor with ion B × ∇B away from the X-point in the DIII-D tokamak. (1st December 2022) - Ma, X.; Wang, H.Q.; Guo, H.Y.; Leonard, A.; Maurizio, R.; Meier, E.T.; Ren, J.; Stangeby, P.C.; Sinclair, G.; Thomas, D.M.; Wilcox, R.S.; Yu, J.H.; et al.
Abstract: An electron temperature bifurcation is observed in the small angle slot divertor, which has been developed to enhance neutral cooling across the divertor target by coupling a closed slot structure with appropriate target shaping. Experiments in the DIII-D tokamak and associated SOLPS-ITER modeling with full drifts find a strong interplay between drifts and divertor geometry on divertor dissipation. The coupling of divertor geometry and drift flows can strongly affect the path towards divertor detachment onset as the plasma density is raised. With the strike point on the inner slanted surface and ion B × ∇ B away from the magnetic X-point, bifurcative transitions were observed with sharp decrease of T e towards detachment onset both experimentally and computationally. This differs from the situation for the open divertor where the T e cliff was only observed for ion B × ∇ B towards the X-point. SOLPS-ITER modeling with full drifts demonstrates that the magnitude of the E × B drift flow is comparable with the main plasma flow. The reversal of both the poloidal and radial E × B flows near the strike point leads to rapid density accumulation right near the separatrix, which results in bifurcative step transition of divertor conditions with cold plasma across the entire divertor target plate. These results indicate that the interplay between geometry and drifts should be fully taken into account in future fusion reactor divertor designs.